The Role of Entrepreneurial Mindset As A Mediator In The Influence of Experiential Learning on Career Readiness Among Vocational High School Students - Lukmanasari, Herla; F.Danardana Murwani; Triadi Agung Sudarto (International journal of technology and education research, 2025)
The study investigates the direct and indirect influence of Experiential Learning (EL) on Career Readiness (CR), mediated by the dimensions of Entrepreneurial Mindset (Elaborating Mindset, EM1, and Implementing Mindset, EM2) among Vocational High School (SMK) students in Mojokerto, Indonesia. Despite vocational education, SMK graduates still face high unemployment, highlighting a competency gap. This quantitative study used a descriptive explanatory design with a sample of 377 Grade XII students from four Mojokerto SMKs. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The novelty lies in examining EM's two dimensions as a mediator in the EL-CR relationship within this specific context. Results confirm a positive and significant direct influence of EL on CR, EM1, and EM2, and a positive and significant influence of both EM1 and EM2 on CR. Crucially, EM1 and EM2 significantly and partially mediate the EL-CR relationship. The main implication is that hands-on experience (EL) must be complemented by the development of reflective and execution-oriented thinking (Entrepreneurial Mindset) to optimally enhance student readiness for the challenging job market